Analisis Pengaplikasian Kurikulum Merdeka: Penggunaan E-Rapor Sebagai Alat Evaluasi di SMAN 1 Cikarang Selatan - Siti Asiah; Nur Lutfiyana (Jurnal Multidisiplin Ibrahimy, 2024)
This research is motivated by the E-Rapor Kurikulum Merdeka application at SMAN 1 Cikarang Selatan as the object of research seen from the method of use, application features. Processing and filling in this application shows changes in evaluation tools from manual to digital and dealing with the post-covid 19 pandemic situation. Then, this research is limited by several research questions in the form of problem formulations containing the reasons for using this application; advantages and disadvantages of the application; user responses to the application; and to what extent this application provides teacher satisfaction as users. Furthermore, this research uses a qualitative approach with a descriptive method, namely a method that focuses on problems based on facts carried out by means of observation, interviews, and studying documents. In addition, to deepen the analysis, Usability analysis is used with several aspects developed as indicators: Learnability, Efficiency, Memorability, Error, and Satisfaction. These five aspects are used as a reference as a way to analyze how effectively this application is used and the weaknesses in it. The Merdeka Curriculum E-Rapor application applied at SMAN 1 Cikarang Selatan after being studied showed that this application is easy to use, user friendly, and errors experienced personally as users are not in the application. In terms of efficiency, when logging out. The security aspect of this application is very good and cannot be logged in carelessly on the device, because it will make the account unable to log back in and must ask the operator to reset the account, easy to open and run, quick to master its use, according to user expectations, appropriate, complete features, easy to access, easy to remember, difficulty logging out, closing the window cannot access login.